Effect of different BAP concentration and shoot decapitation on in vitro axillary proliferation of Gynura procumbens - Shaari, Nur Iffah (2018)
'Sambung nyawa' or Longevity spinach with the scientific name Gynura procumbens is a medicinal plant belonging to Asteraceae family. This herb is commonly found in tropical Asia countries such as China, Thailand, Indonesia, Malaysia, and Vietnam. It contains bioactive compounds such as flavonoids and glycosides and has potential in treating hypertension, diabetes, infertility, cancer and inflammation. Currently, this plant can be propagated using stem cutting and seedling but the problem is limited number of planting material can be produced and slow germination rate using seedling. At present, there are not much research been reported on plant tissue culture of G. procumbens. Therefore, these experiments are carried out with the objectives to investigate the effect of different BAP concentration (0, 2.0, 5.0 and 10.0 mg/L) and shoot decapitation on in vitro axillary proliferation of G. procumbens. The culture media used for both experiment is Murashige and Skoog (1962) medium. All BAP treatments including the control treatment produced 100% of shoot regeneration. The medium with supplemented with 2.0 mg/l BAP triggered the highest shoot proliferation per explant with 4.22 shoot formed per explant. Shoot tip decapitation triggers significantly shoot proliferation compared with non-decapitation treatment. It is recommended that sub-culturing of shoots be carried out after 6 weeks of culture.